2006
DOI: 10.1021/jm060797q
|View full text |Cite
|
Sign up to set email alerts
|

Further Synthetic and Biological Studies on Vitamin D Hormone Antagonists Based on C24-Alkylation and C2α-Functionalization of 25-Dehydro-1α-hydroxyvitamin D3-26,23-lactones

Abstract: An efficient synthesis and the biological evaluation of 80 novel analogs of 25-dehydro-1alpha-hydroxyvitamin D3-26,23S-lactone 2 (TEI-9647) and its 23R epimer (3) in which the lactone ring was systematically functionalized by introduction of a C1 to C4 primary alkyl group at the C24 position (5 sets of 4 diastereomers), together with their C2alpha-methyl, 3-hydroxypropyl, and 3-hydroxypropoxy-substituted derivatives were described. The triene structure of the vitamin D3 was constructed using palladium-catalyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 50 publications
(104 reference statements)
0
31
0
Order By: Relevance
“…In the case of (23S, 24S) isomers (2, 6, and 18), their R 1 substituents are big enough to touch this green contour, which enhance their antagonistic activities to be 2.2, 3.5 and 1.7-fold higher potencies than that of 1. [28] We can see that this large green area lies just below the large yellow contours, indicating moderate groups are preferred to the inhibitory activity while bulky groups may touch the yellow polyhedron and decrease the activity. A case point is that compound 51 has a little stronger potency than that of 55.…”
Section: Steric Fieldmentioning
confidence: 92%
See 3 more Smart Citations
“…In the case of (23S, 24S) isomers (2, 6, and 18), their R 1 substituents are big enough to touch this green contour, which enhance their antagonistic activities to be 2.2, 3.5 and 1.7-fold higher potencies than that of 1. [28] We can see that this large green area lies just below the large yellow contours, indicating moderate groups are preferred to the inhibitory activity while bulky groups may touch the yellow polyhedron and decrease the activity. A case point is that compound 51 has a little stronger potency than that of 55.…”
Section: Steric Fieldmentioning
confidence: 92%
“…Since the experimental values [28] were given as relative antagonistic activities, we converted them to the absolute values of IC 50 (in nM) based on the data of compounds 1 (IC 50 is 6.3 nM) and 13 (IC 50 is 0.0074 nM), as listed in Table 1. The converting details are described by the note in Table 1.…”
Section: Data Sets and Biological Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Both vitamin D 3 analogs 15 and 16, which have an ␣-methylene-␥-butyrolactone part on the side-chain, are the first specific antagonists of VDR-mediated genomic action of 1, and 15 with 23S-configration has stronger antagonism (IC 50 9.4 nM) than 16 with 23R-configration (IC 50 134.3 nM). After our synthetic studies on the C2␣ and C24-double functionalization of 15 and 16 to investigate the structure-activity relationships, we found that 2␣-(3-hydroxypropoxy)-24-propyl-25-dehydro-1␣-hydroxyvitamin D 3 -26,23-lactone (17) showed the strongest VDR antagonism, as far as we know, and its IC 50 value was 7.4 pM to inhibit differentiation of human leukemia cells (HL-60 cells) induced by 10 nM of 1 [51].…”
Section: Designed Ligands For Paget's Diseasementioning
confidence: 99%